Nesodiprion orientalis sp. nov., N. japonicus, and N. biremis, with a key to species of Nesodiprion (Hymenoptera, Diprionidae) - Hara, Hideho; Smith, David R. (Zootaxa, 2012)
Nesodiprion japonicus (Marlatt, 1898), the type species of Nesodiprion, from Japan, Korea, and Taiwan, and N. biremis (Konow, 1899) from China are redescribed based on their type specimens. Lectotypes are designated for both. Nesodiprion orientalis Hara & Smith, sp. nov. is described from Thailand and Yunnan Province, China. Larvae of all three species feed on Pinus. Generic characters of Nesodiprion are discussed, and a provisional key to species of the genus is given.